Optimization and validation of potassium hydrogen phthalate coulometric titration: A potentially primary method (2023)
The implementation of primary quantification methods in the National Metrology Institute of Colombia (INM) will allow the certification of reference materials (CRMs) required by Colombia's industrial and scientific fields. One of these materials is potassium hydrogen phthalate (KHP). Furthermore, coulometry is a well-known potentially primary method because it directly relates the amount of substance to the international system of units (SI). Therefore, we implemented a coulometric system for KHP quantification. Also, a nonlinear regression to the experimental data was made with two models, an exponential W-function (eWf) and our proposal, the theoretical titration curve (TC). One of the main advantages of the TC is the possibility to study and correct the effect of CO2 as the main impurity in the coulometric system. Additionally, the TC allows us to directly estimate the KHP concentration without estimating the endpoint time. On the other hand, using a coulometer developed in this work (CC), we have found that the TC has a better relative uncertainty (0.102 %) compared to the eWf (0.247 %). We also studied the coulometric cell geometry, vertical and horizontal, with two convection modes, ultrasound and magnetic stirring. We obtained no statistical difference between the cell geometry in the amount of substance, and the best convection mode is still magnetic stirring. Finally, using the coulometer developed in INM of Colombia (CC) and the TC, we decreased the uncertainty and bias of the amount of substance of KHP obtained by coulometric titration with respect to the results obtained in the INM of Colombia in the intercomparison study between national metrology institutes in 2016.